The Implications of Extending the Term of the Village Head on the Sustainability of Governance in Village Development in Purwakarta Regency from the Maslahah Mursalah Perspective - Syahna Rahmawati Dewi; Lutfi Fahrul Rizal; Muhammad Amin (al-Afkar, Journal For Islamic Studies, 2025)
The extension of the village head's term of office from 6 years to 8 years based on Law Number 3 of 2024 raises various implications for the sustainability of village government, especially in the implementation of development. This study aims to analyze the impact of this policy on village development in Purwakarta Regency using the Maslahah Mursalah perspective. The research was conducted through a qualitative method with a juridical-empirical approach, using interview, observation, and documentation techniques. The research location focused on two villages with different statuses, namely Ciwareng Village (independent) and Malangnengah Village (developing). The results of the study show that a longer term of office can be beneficial if supported by visionary, participatory leadership, and a strong monitoring system, such as in Ciwareng Village. Conversely, without accountable leadership and good community participation, as in Malangnengah Village, this policy has the potential to cause harm in the form of development stagnation and weak village governance. Thus, the policy of extending the term of office of the village head will only be beneficial if accompanied by a sustainable evaluation and accountability mechanism.